Dimorphism in Neopseudocercosporella capsellae, an Emerging Pathogen Causing White Leaf Spot Disease of Brassicas - Gunasinghe, Niroshini; Barbetti, Martin J.; You, Ming Pei; Dehigaspitiya, Prabuddha; Neate, Stephen (Frontiers in Cellular and Infection Microbiology, 2021)
White leaf spot pathogen: Neopseudocercosporella capsellae causes significant damage to many economically important Brassicaceae crops, including oilseed rape through foliar, stem, and pod lesions under cool and wet conditions. A lack of information on critical aspects of the pathogen’s life cycle limits the development of effective control measures. The presence of single-celled spores along with multi-celled conidia on cotyledons inoculated with multi-celled conidia suggested that the multi-celled conidia were able to form single-celled spores on the host surface. This study was designed to demonstrate N. capsellae morphological plasticity, which allows the shift between a yeast-like single-celled phase and the multi-celled hyphal phase. Separate experiments were designed to illustrate the pathogen’s morphological transformation to single-celled yeast phase from multi-celled hyphae or multi-celled macroconidia in-vitro and in-planta. Results confirmed the ability of N. capsellae to switch between two morphologies (septate hyphae and single-celled yeast phase) on a range of artificial culture media (in-vitro) or in-planta on the host surface before infection occurs. The hyphae-to-yeast transformation occurred through the production of two morphologically distinguishable blastospore (blastoconidia) types (meso-blastospores and micro-blastospores), and arthrospores (arthroconidia).